The Novel Member of the BCL2 Gene Family, BCL2L12, Is Substantially Elevated in Chronic Lymphocytic Leukemia Patients, Supporting Its Value As a Significant Biomarker - Papageorgiou, Sotirios G. (AlphaMed Press, 2011)
BCL2L12 is a recently identified gene belonging to the BCL2 family, members of which are implicated in hematologic malignancies, including chronic lymphocytic leukemia (CLL). The aim of this study was to analyze the mRNA expression of the novel apoptosis-related gene BCL2L12 in patients with CLL and to examine its prognostic and predictive value and potential clinical application as a novel molecular biomarker for CLL. For this purpose, total RNA was isolated from peripheral blood of 65 CLL patients and 23 healthy donors. An ultrasensitive quantitative real-time polymerase chain reaction methodology for BCL2L12 and BCL2 mRNA quantification was developed using SYBR Green chemistry. After preparing cDNA by reverse transcription, relative quantification analysis was performed using the comparative C(T) (2(−ΔΔCT)) method. Furthermore, analysis of IGHV mutational status, CD38 expression, and detection of early apoptosis by double staining with Annexin V-FITC and propidium iodide were performed. According to our findings, BCL2L12 mRNA expression is significantly higher in CLL patients than in healthy donors. Receiver operating characteristic analysis demonstrated that BCL2L12 expression had significant discriminatory value, distinguishing very efficiently CLL patients from the non-leukemic population. Moreover, BCL2L12 expression predicts the presence of CLL, as demonstrated by both univariate and multivariate logistic regression analyses. Finally, high BCL2L12 mRNA levels are associated with advanced clinical stage and predict shorter overall survival in CLL patients.